Evaluasi Dampak Ekonomi dari Pengurangan Ketergantungan pada Impor Migas di Indonesia - Edy Soesanto; Anis Riski Yulianti; Alffin Suherzan (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Indonesia's dependence on oil and gas imports has become a significant challenge to the country's economic stability, with impacts on the trade deficit, global energy price fluctuations, and fiscal dependence. This study aims to evaluate the economic impact of efforts to reduce Indonesia's dependence on oil and gas imports, focusing on the implications for economic growth, trade balance, and national energy security. The methods used include secondary data analysis, macroeconomic modeling, and simulation of the impact of energy policies such as increasing domestic oil and gas production, energy diversification, and renewable energy development. The results show that reducing dependence on oil and gas imports has the potential to reduce pressure on the trade balance and foreign exchange reserves, and improve long-term energy security. However, the transition to domestic energy security requires large investments in the renewable energy sector, supporting infrastructure, and policies that support energy efficiency. This study suggests the need for an integrated policy strategy between the government, private sector, and society to achieve the goal of reducing oil and gas dependence and improving Indonesia's economic competitiveness.